Review of Development Activity in Uttar Pradesh 1965-66 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1965)
This report attempts to review the progress of development activities in the State during the year 1965-66 up to the quarter ending March 31, 1066, i.e. from April 1, 1905 to March 1966. It relates only to such development schemes as are included in district Plans, The review excludes throe border districts of Uttarakhand Division and covers remaining 51 districts of the State with 851 active blocks and is based on Divisional Quarterly Progress Reports. The 854 active blocks covers approximately 98 per cent of the total area ; 86 percent of the total population ; and 99 per cent of the rural population of the State excluding Uttarakhand Division.
Community Development Department , Government of Uttar Pradesh